Influence Of Financial Technology (Fintech) On Msme Financial Performance In Gorontalo City - Muhammad Fuad Alamsyah; Rifka Nurul Islami (Economics and Digital Business Review, 2023)
This study aimed to find the influence of Financial Technology in the form of Capital Loans (X1), Digital Payment Services (X2), and Financial Regulatory Services (X3) on the Financial Performance (Y) of the MSME “Boutique” in Gorontalo City. This study used quantitative methods. The analytical method employed in this study was path analysis using SPSS version 23. The results showed that Financial Technology in the form of capital loans (X1) influenced the Financial Performance (Y) of the MSME “Boutique”. Digital Payment Services (X2) influenced the Financial Performance (Y) of the MSME “Boutique”. Financial Regulatory Services (X3) influenced the Financial Performance (Y) of the MSME “Boutique”.